1994
DOI: 10.1111/j.1365-2621.1994.tb02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid loss and sensory changes in intermediate moisture pineapple during storage at 30–40°C

Abstract: Kinetics of ascorbic acid loss as a function of storage temperature (30, 35 and 40°C) and water activity of intermediate moisture pineapple slices at a, of 0.92, 0.95 and 0.97 was modelled. Loss was faster at higher a,,, but storage temperatures of 30-40°C had little effect at the same a,,,. Colour changes were larger than flavour changes. Spoilage was only a problem at high a,.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Nevertheless, the effect of the drying temperature on the compression characteristics of durian chips was found insignificant (Jamradloedluk et al, 2007). Degradation rate of ascorbic acid is affected by several factors such as temperature, water activity, pH, storage time and metal ions (Fennema, 1993;Pardio Sedas et al, 1994). The retention of ascorbic acid during vegetable drying is a function of process conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the effect of the drying temperature on the compression characteristics of durian chips was found insignificant (Jamradloedluk et al, 2007). Degradation rate of ascorbic acid is affected by several factors such as temperature, water activity, pH, storage time and metal ions (Fennema, 1993;Pardio Sedas et al, 1994). The retention of ascorbic acid during vegetable drying is a function of process conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Santos and Silva (2009) studied the effect of ethanolic atmosphere on the degradation kinetics of ascorbic acid and the drying behavior of pineapple. Pardio Sedas et al (1994) studied ascorbic acid loss in pineapple during storage under fixed conditions of temperature and relative humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, they have also reported that pineapple dried at 45 °C showed better rehydration ability and more l -ascorbic acid retention than those obtained by air drying at 75 °C. Other authors have also studied the drying behavior of pineapple and the loss of ascorbic acid in pineapple during drying and storage under different conditions. , Izli et al have investigated the effect of convective (60, 70, 80 and 90 °C), microwave (120 and 350 W), and freeze drying methods on the drying kinetics, color, total phenolic (TP) content, and antioxidant capacity of pineapples. Their results showed that the pineapple dried with freeze drying and microwave drying had the best antioxidant capacity and total phenolic content value.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on the ascorbic acid loss in vegetables during storage under fixed conditions of temperature and relative humidity [8; 9; 10] . [11] developed an empirical equation to predict ascorbic acid degradation in pineapple as a function of storage temperature and water activity. Also, Sunmonu et al, 2013 developed empirical models equations [12] for prediction of nutritional parameters of stored bananas.…”
Section: Introductionmentioning
confidence: 99%